Dysmobility Syndrome and Risk of Mortality for Community-Dwelling Middle-Aged and Older Adults: The Nexus of Aging and Body Composition - Wei-Ju Lee (Nature Portfolio, 2017)
Abstract Dysmobility syndrome is a newly proposed concept to comprehensively consider bone-muscle-adiposity as a whole to associate with mortality and other adverse outcomes in the older adults. Little was known in Asian populations since the body composition was highly related to ethnicity. The study aimed to evaluate the association between dysmobility syndrome and mortality and to explore the most optimal operational definition for dysmobility syndrome. The prevalence of dysmobility syndrome was 3.9–10.1% based on different operational definitions of adiposity and skeletal muscle index. Subjects with dysmobility syndrome were older, more often to be women, having higher adiposity, lower lean body mass and bone mineral density. Multivariate Cox proportional hazard model showed that dysmobility and pre-dysmobility syndrome had higher risk of mortality than the robust group (Hazard ratio (HR): 11.3, 95% confidence interval (CI): 1.2–109.1; and HR 8.7, 95% CI 1.1-67.3, respectively). Overall, the modified operational definition of dysmobility syndrome in Asian populations using FNIH-adjusted skeletal muscle mass and waist circumference-defined adiposity may be the most optimal model for mortality prediction. Taking the nexus of body composition as a whole to evaluate the mortality risk of older adults is an important improvement beyond sarcopenia and osteoporosis.